The female labor world and psychology: from vocational guidance to job placement for institutionalized girls and youth - Josiane Suelí Béria; Fernando Andres Polanco (Interacciones)
The present article journal from the local area. The results show that in the labor field we investigated vocational orientation and those of institutionalized infants. The work is shown with a clear division of gender and social class a historiographical study on the feminine labor world in San Luis, Argentina, from 1951 to 1965. The data were collected and analyzed of Anales del Instituto de Investigaciones Pedagógicas/Psicopedagógicas. We seek to give a general overview from the epistemic and extra-epistemic discourses, present in the research published in this scientific journal from the local area. The results show that in the labor field we investigated vocational orientation and those of institutionalized infants. The work is shown with a clear division of gender and social class.